Terapi Genggam Bola Karet Pada Lansia yang Mengalami Stroke di Taman Bodhi Asri Binjai - Martina, Siska Evi; Gultom, Rumondang; Sinaga, Janno; Yonggiana; Rahmadani, Fitria; Marbun, Kesia Lina Uli; Annisa; Febrianda, Nuriasma (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Muscle weakness in the upper extremities is a common consequence of stroke that can impede daily activities such as eating, bathing, dressing, and controlling incontinence. Stroke patients with muscle weakness are highly dependent on assistance from others for their daily routines. An effective intervention to enhance muscle strength in stroke patients is the use of rubber ball grasping therapy. This therapy involves using an elastic rubber ball that can be easily compressed with minimal force, making it safe and user-friendly. The primary objective of this therapy is to stimulate hand motor skills by repeatedly clenching the rubber ball. This method aims to increase muscle strength by stimulating muscle fibers to contract. The advantage of using a rubber ball for this therapy lies in its availability and the ease with which it can be conducted in various settings, offering flexibility for implementation. This study aims to evaluate the effectiveness of rubber ball grasping therapy for elderly stroke patients at Taman Bodhi Asri Binjai.